Thermal, spectroscopic and antimicrobial activity characterization of some norfloxacin complexes - Nunes, Wilhan Donizete Gonçalves [UNESP]; do Nascimento, André Luiz Carneiro Soares [UNESP]; Moura, Aniele [UNESP]; Gaglieri, Caroline [UNESP]; Vallim, Gustavo Brunelli; Nascimento, Luiz Carlos; Mendes, Roni Antônio; Ionashiro, Massao [UNESP]; Caires, Flávio Junior [UNESP] (Springer Nature, 2018)
Coordination compounds of transition metals with norfloxacin (Nor) have potential to improve its effectiveness, as already discussed for some compounds found in the literature. The complexes in the solid state were prepared by precipitation of the respective metal cation (M = Mn(II), Co(II), Ni(II), Cu(II) and Zn(II)) with a norfloxacin sodium salt solution. The thermal behavior under oxidative and pyrolysis conditions was investigated employing thermogravimetry and differential thermal analysis (TG/DTG–DTA) and evolved gas analysis (EGA/TG-FTIR), and the complexes were characterized by elemental analysis (EA), EDTA complexometric titration, infrared spectroscopy (FTIR) and X-ray powder diffraction (XRD). By these results, the minimum formula was established as [M(Nor)2(H2O)2]·nH2O, where n = 3 (Ni), 2.5 (Mn Co, Zn), or 2 (Cu). The evolved gases identified during thermal decomposition of Ni and Cu complexes were ethylene, CO2 and CO for Ni; CO2 and ethane for Cu. Also, antimicrobial activity of the complexes was evaluated by in vitro susceptibility test using the agar diffusion method, and the results were compared with the uncomplexed molecule. It was found that norfloxacin complexation modifies its antibacterial activity. The activity depends on the type of metal ion and microorganism; Mn(II), Co(II) and Zn(II) complexes significantly increased activity against the tested gram-negative bacteria.
Keywords: Antibacterial activity; Complexes; Norfloxacin; Thermal behavior